Antiretroviral Therapy Use Among HIV-Infected Men who have Sex with Men Attending a Sexually Transmitted Diseases Clinic - Dombrowski, Julia C. (2010)
We examined antiretroviral therapy (ART) use among 501 previously diagnosed HIV-infected men who have sex with men who sought care at an STD Clinic in King County, WA during 2004–2008. Overall, 42% of men were not taking ART, 71% of whom had CD4 counts >350 cells/µL. Of those who reported unprotected anal intercourse with a partner of nonconcordant HIV status in the prior year, 48% were not taking ART (78% with CD4 counts >350 cells/µL). STD Clinics may be an important venue in which to identify persons who are not taking ART. Treating these persons could help diminish HIV transmission.